PERAN MASJID DAN KOMUNITAS MUSLIM DALAM KONSERVASI LINGKUNGAN - Rajiman; Abdullah Ali Ridho Al-Haddad; Asep Rahmatullah (STKIP Subang, 2026)
The global ecological crisis, marked by climate change, land degradation, and domestic waste pollution, demands cross-sectoral responses, including from religious institutions that have long been positioned primarily as ritual spaces. This article examines the transformation of the mosque's and Muslim community's role from a center of worship into an agent of environmental conservation through the eco-mosque movement in Indonesia. Using a qualitative-descriptive approach combining literature review and religious-ecological discourse analysis, supported by documentary observation of eco-mosque practices at several pilot mosques, this study analyzes primary data (eco-mosque program documentation, Indonesian Ulema Council/MUI environmental fatwas and regulations) and secondary data (accredited literature) through triangulated content analysis and critical discourse analysis. This study argues that theological reinterpretation of khalifah fil ardh (vicegerency), mizan (cosmic balance), and fiqh al-bi'ah (environmental jurisprudence) provides an epistemological foundation for mosques to actively engage in wastewater management, waste banks, energy efficiency, and greening initiatives. The social capital held by religious study circles (majelis taklim), mosque youth organizations, and Islamic mass organizations proves to be an effective lever for collective mobilization in community-based conservation movements. These findings imply the need to integrate ecological values into the Islamic Religious Education (PAI) curriculum as a foundation for cultivating environmental character from an early age. This article recommends strengthening the policies of the Indonesian Mosque Council (DMI) and PAI educators in mainstreaming environmental jurisprudence as an integral part of contemporary Islamic da'wah and education.